CALCULATING THE MECHANICAL CHARACTERISTICS OF AN INDUCTION MOTOR AND ADJUSTING THE SPEED - Mirzayev Uchqun; Istamov Og‘abek (Лучшие интеллектуальные исследования, 2024)
This paper analyzes data on methods for calculating the mechanical characteristics of asynchronous machines.